The impact of busy boards on earnings management: A case study of estate companies listed on the Vietnamese stock exchange - Nhan-Anh Thi Cao; Ngoc Tien Nguyen (Decision Science Letters)
While busy boards have been widely studied in corporate governance, research on this topic in Vietnam is lacking. In the real estate sector, where high leverage and regulatory challenges per-sist, busy boards may impact earnings management (EM). This study explores their influence on EM in listed Vietnamese real estate firms, contributing to corporate governance insights. This research aims to investigate the presence of busy boards and Board of Directors (BOD) character-istics on EM behavior. This research employs the OLS, FEM, REM and Generalized Least Squares (GLS) regression model to analysis. Analysis results show that the number of busy boards has a positive impact on EM behavior. The results of this study extend the composite measure of BOD in Vietnam by adding a new factor, which has not been included in previous studies, namely busy boards. Thereby, it helps to improve corporate governance in controlling the "performance results" of the board of directors. Busy boards influence positively EM and oth-er factors: board size, board independence, board expertise, female on board negatively affect EM. The findings of this study demonstrate a relationship between busy boards and EM, subsequently affecting the quality of financial statements. Therefore, the policy makers are recommended to consider comprehensive reviews and possibly "legislate" the advantages of diversity within corpo-rate boards during the drafting, amending, and supplementing of corporate governance regula-tions and rules in Vietnam.